Students' Perceptions of Gender Discrimination in Indonesia: A Study at Muhammadiyah University - Anisia Kumala; Muhammad Dwi Fajri; Muhib Rosyidi; Neng Rahayu; Mutia Salsabila; Amirullah Amirullah (Mimbar Agama dan Budaya, 2024)
Gender equality is still an important and strategic issue to discuss in Indonesia. This study aims to describe the gender role attitudes of students in the Muhammadiyah and Aisyiyah Higher Education (PTMA) environment because PTMA students are agents of change and are tasked with spreading the Muhammadiyah Islamic preaching committed to gender equality and justice. The research method used quantitative with respondents in this study totaling 200 students in various PTMA, 136 women and 64 men. The instruments used in this study were constructed by the researcher and consisted of five dimensions: religion, marriage and family, social work, work, and education. The results of this study indicate that in general, the gender role attitudes of students in the PTMA environment are more egalitarian than traditional gender roles, meaning that they already have a gender role perspective based on equality. However, there is still a gender bias, such as the view of the same potential between women and men in education; religious authority (ulama) towards women is not the same as men; and opportunities for public leadership for women. The implications of the findings of this study will be discussed further.